Food environments select microorganisms based on selfish energetic behavior - Mora, Diego; Arioli, Stefania; Compagno, Concetta (Frontiers in Microbiology, 2013)
Nutrient richness, and specifically the abundance of mono- and disaccharides that characterize several food matrixes, such as milk and grape juice, has allowed the speciation of lactic acid bacteria and yeasts with a high fermentation capacity instead of energetically favorable respiratory metabolism. In these environmental contexts, rapid sugar consumption and lactic acid or ethanol production, accumulation and tolerance, together with the ability to propagate in the absence of oxygen, are several of the ‘winning’ traits that have apparently evolved and become specialized to perfection in these fermenting microorganisms. Here, we summarize and discuss the evolutionary context that has driven energetic metabolism in food-associated microorganisms, using the dairy species Lactococcus lactis and Streptococcus thermophilus among prokaryotes and the bakers’ yeast Saccharomyces cerevisiae among eukaryotes as model organisms.